Alvin Plantinga - Baker, Deane-Peter 1972- (Contemporary philosophy in focus, 2007)
Few thinkers have had as much impact on contemporary philosophy as has Alvin Plantinga. The work of this quintessential analytic philosopher has in many respects set the tone for the debate in the fields of modal metaphysics and epistemology and he is arguably the most important philosopher of religion of our time. In this volume, a distinguished team of today's leading philosophers address the central aspects of Plantinga's philosophy - his views on natural theology; his responses to the problem of evil; his contributions to the field of modal metaphysics; the controversial evolutionary argument against naturalism; his model of epistemic warrant and his view of epistemic defeat; and his recent work on mind-body dualism. Also included is an appendix containing Plantinga's often referred to, but previously unpublished, lecture notes entitled 'Two Dozen (or so) Theistic Arguments', with a substantial preface to the appendix written by Plantinga specifically for this volume